2013
DOI: 10.1021/jf4004434
|View full text |Cite
|
Sign up to set email alerts
|

α-Mangostin: Anti-Inflammatory Activity and Metabolism by Human Cells

Abstract: Information about the anti-inflammatory activity and metabolism of α-mangostin (α-MG), the most abundant xanthone in mangosteen fruit, in human cells is limited. On the basis of available literature, we hypothesized that α-MG will inhibit the secretion of pro-inflammatory mediators by control and activated macrophage-like THP-1, hepatic HepG2, enterocyte-like Caco-2, and colon HT-29 human cell lines, as well as primary human monocyte-derived macrophages (MDM), and that such activity would be influenced by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 53 publications
(178 reference statements)
1
61
0
Order By: Relevance
“…Pre-clinical studies with purified α-MG, the major constituent of the pericarp of mangosteen, have demonstrated its beneficial effects against infections, cancer, memory impairment and asthma (Jang et al, 2012;Sattayasai et al, 2013;Hafeez et al, 2014;Huang et al, 2014). In addition, in vitro studies have demonstrated anti-inflammatory properties of α-MG (Bumrungpert et al, 2010;Liu et al, 2012;Gutierrez-Orozco et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-clinical studies with purified α-MG, the major constituent of the pericarp of mangosteen, have demonstrated its beneficial effects against infections, cancer, memory impairment and asthma (Jang et al, 2012;Sattayasai et al, 2013;Hafeez et al, 2014;Huang et al, 2014). In addition, in vitro studies have demonstrated anti-inflammatory properties of α-MG (Bumrungpert et al, 2010;Liu et al, 2012;Gutierrez-Orozco et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-mangostin (α-MG) is a natural xanthone that has been shown to have anti-oxidant and anti-inflammatory activity in numerous in vitro studies (Williams et al, 1995;Pedraza-Chaverri et al, 2008;Gutierrez-Orozco et al, 2013;Sattayasai et al, 2013). In vivo studies addressed the bioavailability as well as anti-oxidant, anti-cancer and anti-malarial effects of α-MG in rodents (Johnson et al, 2012;Choi et al, 2014;Hafeez et al, 2014;Upegui et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Using a digestion/Caco-2 human intestinal cell model, Bumrungpert et al [125] demonstrated that (i) α-MG was taken up by Caco-2 cells in a dose-dependent manner and partially converted into phase II metabolites, and (ii) both free and conjugated forms of α-MG were transported across the basolateral membrane of Caco-2 cells, suggesting that this compound and its phase II metabolites were absorbed and bioavailable. Subsequently, α-MG was detected to be transported into various cell lines (macrophage-like THP-1, hepatic HepG2, enterocyte-like Caco-2, and colon HT-29), where it underwent phase II metabolism and biotransformation to get converted into other xanthones [126]. By in vitro metabolism studies using tissue homogenates, α-MG was proven to be metabolized mainly via the liver and small intestine [127,128].…”
Section: Molecular Modeling and Docking Studymentioning
confidence: 99%
“…It is noteworthy that bioconversion of α-MG to other xanthones occurred in cultures of the cell lines, but not in primary cultures of human monocyte-derived macrophages. Among the xanthones identified in cultures were garcinone C (Caco-2 and HT-29 cells), garcinone D (THP-1 and HT-29 cells) and 9-hydroxycalabaxanthone (HepG2 and Caco-2 cells) [8]. …”
Section: Metabolism and Bioavailability Of Mangosteen Xanthonesmentioning
confidence: 99%